Protocol for inducing beige adipocytes in white adipose tissue of mouse using cold exposure and CL316,243 injection - Yalan Wu; Chenguang Wang; Xiao Yu Tian (STAR Protocols)
Summary: White adipose tissue (WAT) beiging holds significant therapeutic potential for combating obesity. Here, we present a protocol for inducing beige WAT in mice using both cold exposure and CL316,243 treatment. We describe steps for intraperitoneal injection, and subcutaneous WAT (sWAT) isolation, dissection, and fixation. We then detail procedures for histology, whole-mount immunofluorescence (IF) staining, and extracting RNA and protein. This protocol can be used for subsequent analysis to explore the mechanisms governing beige WAT induction in experimental settings, particularly the evaluation of angiogenesis.For complete details on the use and execution of this protocol, please refer to Wang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.